(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: Superficial mycotic infections have a global prevalence of 20-25%, with dermatophytes being the most common causative agents. Objective: To explore the association between blood group typing and clinical manifestations of dermatophytosis patients. Methods: This case-control study was conducted using data collected from the outpatient department of Dermatology and Venereology at Kurmitola General Hospital, Dhaka from April 2024 to September 2024. A control group of 115 clinically healthy people and 115 patients with dermatophytosis composed up the 230 participants in total. All subjects were diagnosed by a dermatologist. Blood samples were taken from each participant for ABO blood grouping and Rh typing were evaluated in the hematology laboratory of this hospital. Results: A significant relationship was found between the clinical manifestations of dermatophytosis in males and blood group types. Statistical analysis revealed that tinea pedis had the strongest association with blood groups, with groups B and O being the most affected. Tinea capitis also showed a significant correlation with blood group O, indicating greater susceptibility within this group. Other clinical manifestations did not show a notable correlation with blood group types. In contrast, there was no significant association within blood groups and the clinical manifestations of dermatophytosis in females, except for tinea capitis, which was most significantly associated to blood group A. Conclusion: The study revealed that males with blood group O and females with blood group A were the most commonly infected among dermatophytosis patients. Furthermore, the majority of dermatophytosis patients had Rh (+ve) blood type. Dermatophytosis was found to be significantly associated with blood types in males, specifically with tinea pedis in blood groups B and O and with tinea capitis in blood group O. JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 22-26